Child Labor : A Normative Perspective - Satz, Debra (Washington, DC: World Bank, 2014)
Examining child labor through the lenses of weak agency, distributive inequality, and harm suggests that not all work performed by children is equally morally objectionable. Some work, especially work that does not interfere with or undermine their health or education, may allow children to develop skills they need to become well-functioning adults and broaden their future opportunities. Other work, including child prostitution and bonded labor, is unambiguously detrimental to children. Eliminating these forms of child labor should be the highest priority. Blanket bans on all child labor may drive families to choose even worse options for their children, however. Moreover, child labor is often a symptom of other problems poverty, inadequate education systems, discrimination within families, ethnic conflicts, inadequately protected human rights, weak democratic institutions that will not be eliminated by banning child labor.